Follicular environment as a predictive tool for embryo development and kinetics in cattle - Alves, Gláucia Pereira; Cordeiro, Fernanda Bertuccez; Bruna De Lima, Camila; Annes, Kelly; Cristina Dos Santos, Érika; Ispada, Jéssica; Fontes, Patrícia Kubo [UNESP]; Nogueira, Marcelo Fabio Gouveia [UNESP]; Nichi, Marcílio; Milazzotto, Marcella Pecora (CSIRO Publishing, 2019)
Follicular fluid composition and the transcription pattern of granulosa cells were analysed to better comprehend associations between embryo development and morphokinetics. Bovine follicles were punctured and their respective follicular fluid and granulosa cells were collected. Cumulus-oocyte complexes derived from these follicles were matured and fertilised in vitro. Embryo morphology and kinetics were evaluated at 40 h after insemination, when embryos were classified as fast (FCL, four or more cells), slow (SCL, 2-3 cells) or non-cleaved (NCL). Their development was followed until the blastocyst stage. Glucose, pyruvate, cholesterol and oestradiol were quantified in the follicular fluid and the transcription pattern of 96 target genes was evaluated in granulosa cells by large-scale quantitative reverse transcription polymerase chain reaction. Follicular fluid from the blastocyst group had increased levels of glucose, total cholesterol and pyruvate compared to the non-blastocyst group, whereas higher levels of oestradiol were observed in the follicular fluid of embryos and blastocysts with fast cleavage. The transcriptional pattern revealed altered metabolic pathways between groups, such as lipid metabolism, cellular stress and cell signalling. In conclusion, both follicular fluid and granulosa cells are associated with the possibility of identifying follicles that may generate embryos with high potential to properly develop to the blastocyst stage.
Keywords: bovine; follicular fluid; granulosa cells; morphology; system biology